2006
DOI: 10.1021/ol061604w
|View full text |Cite
|
Sign up to set email alerts
|

Solventless Clay-Promoted Friedel−Crafts Reaction of Indoles with α-Amido Sulfones:  Unexpected Synthesis of 3-(1-Arylsulfonylalkyl) Indoles

Abstract: Friedel-Crafts reaction of indoles with alpha-amido sulfones in the presence of montmorillonite K-10 leads unexpectedly to 3-(1-arylsulfonylalkyl) indoles in good yield. The obtained products can be further desulfonylated under reductive or alkylative conditions giving linear and branched 3-substituted indoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 36 publications
2
68
0
Order By: Relevance
“…The NMR spectra of the products 3aa, [8] 3ba, [8] 3ca, [9] 3da, [10] 3fa, [11] 3ha, [12] 3ja [11] and 3ka [13] are in accordance with those in the literature. concentration were screened, and it was found that only a 1.2:1.0 ratio of indole/benzyl bromide was required for an efficient conversion, thereby preventing the use of a large excess of reagents without any concentration influence.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The NMR spectra of the products 3aa, [8] 3ba, [8] 3ca, [9] 3da, [10] 3fa, [11] 3ha, [12] 3ja [11] and 3ka [13] are in accordance with those in the literature. concentration were screened, and it was found that only a 1.2:1.0 ratio of indole/benzyl bromide was required for an efficient conversion, thereby preventing the use of a large excess of reagents without any concentration influence.…”
Section: Resultssupporting
confidence: 88%
“…[d] The NMR spectra of the products 3aa, [8] 3ab, [14] 3ad, [15] and 3ah [8] are in accordance with those in the literature.…”
Section: Resultssupporting
confidence: 85%
“…The acid catalyzed reaction of indoles requires careful control of the acidity to prevent unwanted side reactions, such as dimerization and polymerization [41,42]. The clay promoted FriedelCraft alkylation of indole to enone and amido sulfones were also investigated [43,44]. Michael addition of indoles to enones was also investigated over photoinduced 1,4-additions [45].…”
Section: Introductionmentioning
confidence: 99%
“…A plausible mechanism for the formation of 14 may start from the N-acyliminium ion B (Figure 1) formed by elimination of arenesulfinic acid from the α-amido sulfone 13 through the action of the Fe III in FeCl 3 ·6 H 2 O. A reaction between the strong electrophile B and 1,2,4-trimethoxybenzene (9) would then give the Friedel-Crafts product C. Fe III could catalyze the elimination of carbamate from C, leading to the formation of oxonium ion D. [16] The oxonium ion D could then react once more with 1,2,4-trimethoxybenzene (9), giving rise to the bis-arene E through the reversible reaction. The formation of the bis-arene E was observed by TLC (just above the spot for the desired product) during the course of the reaction but had completely disappeared at end of the reaction.…”
Section: Resultsmentioning
confidence: 99%